Natural Products for Chemoprevention of Breast Cancer - Ko, Eun-Yi (J Cancer Prev, 2015)
Breast cancer is the primary cause of cancer death in women. Although current therapies have shown some promise against breast cancer, there is still no effective cure for the majority of patients in the advanced stages of breast cancer. Development of effective agents to slow, reduce, or reverse the incidence of breast cancer in high-risk women is necessary. Chemoprevention of breast cancer by natural products is advantageous, as these compounds have few side effects and low toxicity compared to synthetic compounds. In the present review, we summarize natural products which exert chemopreventive activities against breast cancer, such as curcumin, sauchinone, lycopene, denbinobin, genipin, capsaicin, and ursolic acid. This review examines the current knowledge about natural compounds and their mechanisms that underlie breast cancer chemopreventive activity both in vitro and in vivo. The present review may provide information on the use of these compounds for the prevention of breast cancer.